ANALISIS PEMETAAN MINAT MENJADI GURU PADA MAHASISWA CALON GURU KIMIA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS MULAWARMAN - Syafira, Irmaina; Hartati, Yuli; Erika, Farah (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Someone who has an interest in becoming a teacher will feel happy with their job as a teacher without needing encouragement from other parties. Not all chemistry education study program students aim to become teachers after completing their studies. Many students enter the education department without having a definite desire to become teachers in the future after graduating. This research aims to determine the mapping of interest in becoming a teacher among prospective chemistry teacher students at the Faculty of Teacher Training and Education, Mulawarman University. This research is descriptive qualitative research. The subjects in this research were 68 chemistry education students at Mulawarman University class of 2019. Data were collected using a questionnaire. The data analysis technique used is descriptive analysis technique using percentages. Based on the research results, a mapping of interest among prospective chemistry teacher students was obtained from those who were interested, not interested and who were unsure. Keywords: Teacher, College Student, Interest, Interest in Becoming a Teacher